Luminescence study on the solvation of Cm(III) in binary aqueous solvent mixtures - Trumm, Sascha; Lieser, Georg; Panak, Petra (Radiochimica acta, 2011)
The preferential solvation of Cm(III) in binary aqueous mixtures of MeOH, t BuOH, DMSO, MeCN and acetone is studied at varied solvent composition. Solvation is investigated by time-resolved laser fluorescence spectroscopy and emission spectra and fluorescence lifetime data are obtained. At high mole fractions of organic solvent, preferential solvation of Cm(III) increases in the order: Me 2 CO < t BuOH ≈ MeOH < MeCN < H 2 O < DMSO. Thermodynamic data are derived from the spectroscopic results showing small positive standard Gibbs energies for the transfer of Cm(III) into the various solvent mixtures except for DMSO mixtures where negative values are found. The spectroscopically obtained enthalpies of transfer are fitted to a solvation model using the model parameters Δ Δ Hº 12 and ( αn + βN )º, rendering valuable information on the interaction of Cm(III) with the solvent molecules. Cm(III)-solvent interaction increases in the order: t BuOH < MeCN < MeOH < DMSO.